An environmental scan on the public realtions of the Queen City Development Bank Davao branch - Acampado, Florida Mae T.
This thesis paper involves an environmental scan of the external and the internal public relations of the Queen City Development Bank Davao Branch, in San Pedro St., Davao City, to study its clientele and employee profile, and to know how the bank influenced its current clients and employees. This environmental scan was carried out to identify any points of improvement that the bank can work on. The environmental scan was performed in two ways: 1) The clients were asked to fill out a survey questionnaire about their profile, their knowledge of the bank and its services, and their impressions of the bank and its staff, and 2) The employees were interviewed about their profile, their knowledge of the bank and their line of work, and their relationship with their clients and to their co-workers. The results showed that the clients, who are mostly within the business sector, utilize the word of mouth strategy because it allows them to gather more information and ask any further questions on the topic. As such, even with the bank?s limited promotional material, the bank?s employees are able to promote the bank?s various products and services to possible clients with this strategy. In addition to this, the current clients are exposed to the employees? knowledge and efficiency in their work, approachability, and good customer handling. These clients then promote the bank to relatives and/or acquaintances, and encourage them to avail of the bank?s services as well.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication